Asymmetric Synthesis of Novel Axially Chiral 2, 2′‐Bipyridine N, N′‐Dioxides Bearing α‐Amino Acid Residues and Their Applications in Enantioselective Allylation of Aromatic Aldehydes with Allyltrichlorosilane. Issue 4 (3rd April 2013) - Zhao, Hongwu; Yue, Yuanyuan; Li, Hailong; Sheng, Zhihui; Yang, Zhao; Meng, Wei
Abstract A series of novel axially chiral 2, 2′‐bipyridine N, N′‐dioxides bearing C1 or C2‐symmetry have been synthesized by the use of enantiopure α‐amino acids as chiral sources. The absolute stereochemistry of the axial chirality of these organocatalysts has been clearly assigned by means of CD measurements together with literature protocols. The reactivities and enantioselectivities of these organocatalysts have been examined in the reactions of aromatic aldehydes with allyltrichlorosilane, thus providing the desired products with moderate yields and enantioselectivies.